2019
DOI: 10.1029/2018jb016350
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Shear Wave Velocity Structure of Central Idaho and Eastern Oregon From Ambient Seismic Noise: Results From the IDOR Project

Abstract: We developed 3‐D isotropic crustal seismic velocity models of central Idaho and eastern Oregon from the IDOR (western IDaho and eastern ORegon) Passive seismic data. Ambient noise tomography yielded crustal velocity structure from vertical component Rayleigh wave group and phase velocity measurements. Results include a strong shear wave velocity contrast—faster in accreted Blue Mountains terranes west of the western Idaho shear zone (WISZ), slower in the Idaho batholith, emplaced within the Archean Grouse Cree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…Although there are some hot springs near Stanley (Druschel & Rosenberg, 2001), the moment tensor of the 2020 Stanley earthquake has such a large overall nondouble couple that minor geothermal activity cannot account for it. In addition, strong anisotropy sufficient to affect the long‐period waves used in the moment tensor inversions is unlikely in the shallow crust of the Stanley earthquake region (Bremner et al., 2019; Christian Stanciu et al., 2016). Based on the back‐projection results, InSAR ground deformation and aftershock distribution, we favor a multifault rupture process to explain the significant nondouble‐couple in the moment tensors of the Stanley earthquake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some hot springs near Stanley (Druschel & Rosenberg, 2001), the moment tensor of the 2020 Stanley earthquake has such a large overall nondouble couple that minor geothermal activity cannot account for it. In addition, strong anisotropy sufficient to affect the long‐period waves used in the moment tensor inversions is unlikely in the shallow crust of the Stanley earthquake region (Bremner et al., 2019; Christian Stanciu et al., 2016). Based on the back‐projection results, InSAR ground deformation and aftershock distribution, we favor a multifault rupture process to explain the significant nondouble‐couple in the moment tensors of the Stanley earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…The teleseismic data include 72 P wave and 37 SH-wave ground displacement recordings that are filtered in the frequency band from 0.005 to 0.9 Hz (Figure S3). The structural model used in the inversion is the local model (Bremner et al, 2019;Christian Stanciu et al, 2016;Davenport et al, 2017;Laske et al, 2013 maximum rupture velocity is set to 4 km/s. The subfault durations and rupture velocity are both relatively large for the small subfault dimensions, but this is allowed in order to accommodate the uncertainty in the hypocentral position.…”
Section: Finite-fault Inversion For Teleseismic Datamentioning
confidence: 99%
“…The Stanley earthquake initiated near the intersection of the Idaho Batholith and Basin and Range Province of central Idaho near the northern termination of the Quaternary NWtrending Sawtooth normal fault at its junction with Eocene NE-trending Trans-Challis fault system (Figure 2; . Although these two provinces contain different crustal rocks, regional models suggest similar velocities throughout the epicentral region (Stanciu et al, 2016;Davenport et al, 2017;Bremner et al, 2019).…”
Section: Local Velocity Modelmentioning
confidence: 99%
“…This study also identified reflected returns in the middle to lower crust that may be relevant to this study (e.g., brittle-ductile transition). Bremner et al (2019) used the same station array as the Stanciu et al (2016) study, but utilized surface wave information to derive crustal Vs models. We extracted the closest velocity model to the Stanley earthquake location from each of the three studies to derive our local Vp and Vs models (Figure 3).…”
Section: Local Velocity Modelmentioning
confidence: 99%
“…Although reasonable sound speeds in the atmosphere vary by only a few percent, for example, 322 m/ s < c < 332 m/s (for temperatures −15°C to 0°C), the speeds of the seismic phases that may excite ground displacement are far more variable and less well constrained. Our analysis does not attempt to determine which seismic wave type is most "infrasonogenic," but instead locates sources for a range of potential seismic wave speeds, from P wave velocities of 5.6 km/s to S wave velocities of 3.2 km/s (see Supporting Information S1 analysis as well as the inferred velocity structure below 2 km from Bremner et al, 2019, andDavenport et al, 2017). Modeled surface wave speeds used here are limited to 1.4 km/s or faster given the prevalence of exposed crystalline rock in the region.…”
Section: 1029/2020gl091421mentioning
confidence: 99%